ChemInform Abstract: Total Synthesis of (R, R, R)‐α‐Tocopherol Through Asymmetric Cu‐Catalyzed 1, 4‐Addition. Issue 12 (March 2015) - Termath, Andreas Ole; Sebode, Hanna; Schlundt, Waldemar; Stemmler, Rene T.; Netscher, Thomas; Bonrath, Werner; Schmalz, Hans‐Guenther
Abstract An efficient and conceptually novel synthesis of α‐tocopherol from readily available starting materials is developed.